Pengaruh Variasi Arus Pengelasan SMAW (60, 80 Ampere) Terhadap Kekerasan Logam Las Dan Haz Material Baja ST 37) - Hestukoro, Soni; B.H. Sitorus, Melvin; Salman , Aulia (Indonesian Society of Applied Science, 2024)
This research aims to determine the effect of welding current on the hardness of weld metal and HAZ (heat affected zone) metal which is tested for hardness using the Rockwell method. This research was carried out on ST 37 low carbon steel material which was welded using an E6013 electrode with a diameter of 2.6 mm with a butt joint, then given different welding currents, namely 60, 80, Ampere. For the raw hardness of the low carbon steel material, the average figures were obtained. the average is 48.35 HRB. Specimens that were welded with a current of 60 Ampere had an average weld metal hardness figure of 46.85 HRB and a HAZ of 49.15 HRB. For specimens that were given a welding current of 80 Ampere, the average hardness of the weld metal obtained was 47.05 HRB and the HAZ was 50.3 HRB. The test results show that the increase in hardness numbers in both the weld metal and the HAZ metal is directly proportional to the amount of current used when welding